Connecting Biochemical Photosynthesis Models with Crop Models to Support Crop Improvement - Wu, Alex; Song, Youhong; van Oosterom, Erik J.; Hammer, Graeme L. (Frontiers in Plant Science, 2016)
The next advance in field crop productivity will likely need to come from improving crop use efficiency of resources (e.g. light, water and nitrogen), aspects of which are closely linked with overall crop photosynthetic efficiency. Progress in genetic manipulation of photosynthesis is confounded by uncertainties of consequences at crop level because of difficulties connecting across scales. Crop growth and development simulation models that integrate across biological levels of organization and use a gene-to-phenotype modelling approach may present a way forward. There has been a long history of development of crop models capable of simulating dynamics of crop physiological attributes. Many crop models incorporate canopy photosynthesis (source) as a key driver for crop growth, while others derive crop growth from the balance between source- and sink-limitations. Modelling leaf photosynthesis has progressed from empirical modelling via light response curves to a more mechanistic basis, having clearer links to the underlying biochemical processes of photosynthesis. Cross-scale modelling that connects models at the biochemical and crop levels and utilises developments in upscaling leaf-level models to canopy models has the potential to bridge the gap between photosynthetic manipulation at the biochemical level and its consequences on crop productivity. Here we review approaches to this emerging cross-scale modelling framework and reinforce the need for connections across levels of modelling. Further, we propose strategies for connecting biochemical models of photosynthesis into the cross-scale modelling framework to support crop improvement through photosynthetic manipulation.